2015
DOI: 10.1038/ismej.2015.180
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial reuse of extracellular organic carbon in microbial mats

Abstract: Cyanobacterial organic matter excretion is crucial to carbon cycling in many microbial communities, but the nature and bioavailability of this C depend on unknown physiological functions. Cyanobacteria-dominated hypersaline laminated mats are a useful model ecosystem for the study of C flow in complex communities, as they use photosynthesis to sustain a more or less closed system. Although such mats have a large C reservoir in the extracellular polymeric substances (EPSs), the production and degradation of org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
111
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(118 citation statements)
references
References 58 publications
(44 reference statements)
3
111
0
Order By: Relevance
“…Thus we suggest that the Chloroflexi observed in these mats play an important role in both aerobic and anaerobic carbon cycling, breaking down biomass produced by Cyanobacteria and other photo-and chemoautotrophs. We note that it has also recently been shown that Cyanobacteria themselves may play important roles as heterotrophs respiring organic matter in these systems (Stuart et al 2015).…”
Section: Discussionmentioning
confidence: 66%
“…Thus we suggest that the Chloroflexi observed in these mats play an important role in both aerobic and anaerobic carbon cycling, breaking down biomass produced by Cyanobacteria and other photo-and chemoautotrophs. We note that it has also recently been shown that Cyanobacteria themselves may play important roles as heterotrophs respiring organic matter in these systems (Stuart et al 2015).…”
Section: Discussionmentioning
confidence: 66%
“…In soil [21], sludge and wastewater (referred to as sludge below) [22], and in the phyllosphere [23], microbes are exposed to an abundant—and varying—complex mixture of carbohydrates (e.g., cellulose, xylan, and fructan from plant material and chitin from fungi and arthropods). In aquatic systems (i.e., marine, mats, and larger fresh water environments), the carbohydrate supply is reduced, and chitin is the most common polymer [2426]. Microbes in digestive tracts (i.e., human gut, oral, and most animal samples) are exposed to diverse and abundant substrates including plant polysaccharides and animal glycosaminoglycans found in food and produced by the host [2729].…”
Section: Introductionmentioning
confidence: 99%
“…Sucrose uptake by vegetative cells of Anabaena has previously been reported (40), and sucrose transporters that can also transport maltose are frequently found in plants (41). The Anabaena glucoside transporters could have a role in the recovery of glucosides from extracellular polysaccharides produced under certain physiological conditions, as has been shown to occur in cyanobacterial mats (42). Consistent with this, biomass of the glsC and glsP mutants in old BG11 plates is shiny (not shown), which may be indicative of exopolysaccharide accumulation (33).…”
Section: Discussionmentioning
confidence: 94%